Idiopathic Bone Cavity of Mandibular Symphysis: a Case Report - Lima, Luciano Henrique Ferreira; di Spagna, André Raymundo; Tunel, Fernando Matheus Santana; Sverzut, Alexander Tadeu (ARCHIVES OF HEALTH INVESTIGATION, 2022)
Introduction:An idiopathic bone cavity of the jaw is a rare pseudocyst with unclear etiology and is most commonly found in the body of the mandible. This lesion is generally asymptomatic and incidentally discovered on dental radiographs. Objetives:The aim of this study is to report the case of a 15-year-old male with surgical treatment of this lesion involving the mandibular symphysis, but the vitality pulp was positive. Conclusion: Although there is a non-surgical or surgical option for the treatment of this lesion, the latter is most indicated due to the possibility of a definitive diagnosis and improving bone repair.